The Role of Legal Policies in Shaping Strategic Spatial Planning in North Lampung - Fitria, Shinta; Dwiono, Sugeng (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2025)
The objective of this research is to analyze the implementation of the Regional Spatial Planning in North Lampung, focusing on the strategies for monitoring and controlling spatial planning that involve community participation. The research employs a qualitative methodology, with data collection conducted through interviews, observations, and literature studies. The findings indicate that although the local government has made efforts to involve the community in the decision-making process, the existing participation remains limited and tends to be procedural in nature. This results in a lack of transparency and adequate access to information for the community, which adversely affects the effectiveness of spatial planning. Constraints such as the quality of human resources and the availability of infrastructure also hinder the enhancement of community participation. This study recommends the necessity of strategic measures to actively engage the community at every stage of spatial planning, as well as to improve the community's capacity to understand the importance of their role in spatial management. It is hoped that these findings will contribute to the development of more inclusive and responsive policies that address community needs, while also fostering synergy among the government, the community, and the private sector in achieving sustainable development in North Lampung